Imam Ghazali's Educational Philosophy and Its Relevance to Scocial Science Learning In Primary School - Waseso, Hendri Purbo; Siregar, Maragustam; Sekarinasih, Anggitiyas (Program Pascasarjana Pendidikan Islam Universitas Islam Darul Ulum Lamongan, 2024)
This article aims to reveal the relevance of Imam Ghazali's educational philosophy to elementary/MI social studies learning. Through a literature study using documentation techniques as a collecting technique, the findings are (1) Imam Ghazali's educational philosophy focuses on the final goal of humans, namely the afterlife with worldly media. Apart from that, the key concept that must be understood is that teachers have a heavy responsibility towards students because they are not only responsible for student learning outcomes but also for students' morals, morals and character; (2) SD/MI social studies learning has more contextual characteristics so that the learning process prioritizes direct experience gained by students; (3) the relevance of Imam Ghazali's educational philosophy to elementary/MI social studies learning can be done through the interconnection integration method without dichotomizing its epistemological aspects into the two poles of religious knowledge and general science; and (4) there are two ways to connect Imam Ghazali's educational philosophy and SD/MI social studies learning, namely making Imam Ghazali's spirit or perspective on education the content of social studies learning in elementary/MI indirectly or as a hidden curriculum and reconceptualizing elementary/MI social studies learning MI which is in accordance with Imam Ghazali's views on education.